Evaluasi Tingkat Kematangan Tata Kelola Teknologi Informasi Dan Komunikasi (TIK) Dengan Framework Cobit 5.0 Pada STMIK Pelita Nusantara Medan - Hengki Tamando Sihotang; Harapan Lumbantoruan (Jurnal Mantik Penusa)
In entering competition the quality and predicate best the national and the quality of graduates, college trying to use information technology as an instrument for might win this competition. That information technology can be used in full and supports the system in college, it takes the assessment many it regularly. One method of conducting evaluation of the performance of the department of information technology is to use the framework cobit 5 as yardstick efficiency in the use of information technology currently consisting of 5 ( five ) domain namely: Evaluate, Direct and Organise (EDM),  Align, Plan And Organise (APO), Build, Acquire and Implement (BAI),  Deliver, Service and Support (DSS),  Monitor, Evaluate and Assess (MEA) A measuring instrument his as. With this method, researchers trying to make it blueprint as the end result of utilization of information technology in college , so the management can plan exactly how of development of information technologies company to the next few years .An evaluation, known level capabilities inside the area mea and apo is entirely located at the level of 1 (performed) with the level of the target to be achieved is the level of 3 (established). Weakness governance information technology in STMIK Pelita Nusantara Medan is the lack of formalisasi rules and procedures management information technology. To reduce gap between capability the current level was level and capability to be achieved, so STMIK Pelita Nusantara Medan must meet PA2.1, PA2.2, PA3.1 and PA3.2, that capability the current level was that is at the level of 1 could rise to the level of 3. Along with that, STMIK Pelita Nusantara Medan moved closer to the purpose.Keywords: IT Governance, COBIT 5, Audit, Competency Gap Index (CGI).